Nonradiative Energy Transfer and Photocurrent Enhancements in Hybrid Quantum Dot-MoS2 Devices - Duesberg, Georg; Coleman, Jonathan; Bradley, Louise; Mc Evoy, Niall; Mc Closkey, David (My University, 2018)
The energy transfer mechanism leading to highly efficient nonradiative energy transfer (NRET) from quantum dots (QDs) to monolayer MoS 2 devices has been investigated via a spectral dependence study. The spectral dependence of the NRET from three spectrally separated QD ensembles to monolayer MoS 2 devices reveals that the trends in NRET rates follow the trends in the spectral overlap between the QD emission and MoS 2 absorption spectra, thus verifying that the mechanism for the energy transfer is Förster-type NRET. Furthermore, the dependence of the photocurrent enhancement on the MoS 2 film properties is also explored.
Proceedings of the 20th International Conference on Transparent Optical Networks
2018 20th International Conference on Transparent Optical Networks (ICTON)
PUBLISHED
cited by 1
Keywords: Nonradiative energy transfer; Quantum dots; 2D materials; Photocurrent; Photoresponsivity; Nanoscience & Materials; Nanotechnology